NSD Overexpression in the Fat Body Increases Antimicrobial Peptide Production by the Immune Deficiency Pathway in Drosophila. - Won, C.; Nam, K.; Ko, D.; Kang, B.; Lee, I.S. (International journal of molecular sciences, 2023)
Nuclear receptor-binding SET domain-containing protein 1 (NSD1) inactivation in tumor cells contributes to an immune-cold phenotype, indicating its potential association with immune disturbances. Drosophila NSD is a homolog of the human NSD1. Thus, in this study, we investigated the effect of NSD overexpression in the fat body, the central organ involved in Drosophila immune responses. Upon ectopic expression of NSD in the fat body, the mRNA levels of antimicrobial peptides increased. Using reporter constructs containing deletions of various NF-?B sites in the Attacin-A (AttA) promoter, we found that transcriptional activation by NSD is mainly mediated via the IMD pathway by activating Relish. Since the IMD pathway is required to resist Gram-negative bacterial infections, we further examined the effect of fat body-specific NSD overexpression on Drosophila immune defenses. Upon oral ingestion of Gram-negative Pseudomonas entomophila, the survival rate of the NSD-overexpressing larvae was higher than that of the wild type, suggesting a positive role of NSD in immune responses. Taken together, these results suggest the association of NSD with the IMD pathway and is thus expected to contribute to the elucidation of the molecular mechanisms of immune malfunction in various NSD1-associated human diseases.